Pengaruh Literasi Digital dan Kesadaran Keamanan Siber terhadap Pencegahan Cyber Fraud pada Pengguna Mobile Banking Syariah - Bambang Arianto; Robiatul Auliyah; Izzati Amperaningrum (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2026)
This study aims to examine the effect of digital literacy and cybersecurity awareness on cyber fraud prevention among users of Islamic mobile banking. This issue is important because the development of Islamic digital financial services has grown rapidly, yet it has also been accompanied by increasing cybersecurity risks, such as digital fraud, phishing, personal data theft, account misuse, and illegal transactions that may harm users. This study employed a quantitative approach using a survey method involving 66 respondents who were users of Islamic mobile banking. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software to examine the influence of the independent variables on cyber fraud prevention among Islamic mobile banking users. The findings reveal that digital literacy has a positive effect on cyber fraud prevention. In addition, cybersecurity awareness also has a positive effect on cyber fraud prevention. This study confirms that the better users’ digital literacy, the greater their ability to understand, evaluate, and use Islamic mobile banking services safely. Furthermore, the higher users’ cybersecurity awareness, the greater their ability to prevent potential digital fraud. Therefore, digital literacy and cybersecurity awareness positively influence cyber fraud prevention among users of Islamic mobile banking.